Orchestrating Participatory Learning within Contemporary Educational Ecosystems - M. Agus Kurniawan; Rina Kobayashi (CV JK Riset Publishing Group, 2026)
This study examines the orchestration of participatory learning within increasingly complex and diverse contemporary educational ecosystems. The research background is grounded in the paradigmatic shift from knowledge transmission models toward co-constructive approaches that actively engage learners. The study employed a qualitative methodology with a case study design across three educational institutions in Indonesia, using in-depth interviews, participatory observation, and document analysis. Findings indicate that structured participatory learning significantly enhances learner engagement, develops critical thinking capacities, and strengthens collaborative competencies. The study concludes that successful implementation of participatory learning depends upon facilitator capacity, institutional support, and the design of conducive learning environments. Practical implications encompass recommendations for sustained professional development of educators and curriculum policy reforms responsive to twenty-first-century competency demands.